IGF2 is a potential factor in RAI-refractory differentiated thyroid cancer - Crezee, Thomas (Oncol Lett, 2021)
Differentiated thyroid cancer (DTC) is the most frequent endocrine tumor with a good prognosis after primary treatment in most cases. By contrast, 30–40% of patients with metastatic DTC are unresponsive to (131)I radioactive iodide (RAI) treatment due to tumor dedifferentiation. Currently, underlying molecular mechanisms of dedifferentiation remain elusive and predictive biomarkers are lacking. Therefore, the present study aimed to identify molecular biomarkers in primary tumors associated with RAI refractoriness. A retrospective cohort was gathered consisting of RAI-sensitive patients with DTC and RAI-refractory patients with poorly DTC. In all patients, extensive intratumoral mutation profiling, gene fusions analysis, telomerase reverse transcriptase (TERT) promoter mutation analysis and formalin-fixed paraffin-embedded-compatible RNA sequencing were performed. Genetic analyses revealed an increased mutational load in RAI-refractory DTC, including mutations in AKT1, PTEN, TP53 and TERT promoter. Transcriptomic analyses revealed profound differential expression of insulin-like growth factor 2 (IGF2), with up to 100-fold higher expression in RAI-refractory DTC compared with in RAI-sensitive DTC cases. ELISA revealed significant lower IGF2 plasma concentrations after surgery and subsequent (131)I RAI therapy in patients with DTC compared with pretreatment baseline. Overall, the current findings suggested that the tumor-promoting growth factor IGF2 may have a potential role in acquiring RAI refractoriness.